Effect of some physical factors (Temperature, light intensity) on ability of algae (Scendesmus quadricauda , Chlorella vulgaris) to remove pollutants (Baghdad Science Journal, 2010)
The study included studying some of the optimum environmental conditions(temperature ,light intensity ) on the production of several green algae Scendesmus quadricauda and Chlorella vulgaris in a selected culture and municipal wastewater . The study also included the recording of growth rate ,doubling time and removal of phosphate and nitrate , maximum rate was recorded to the growth with minimum in doubling time and maximum removal rate of nitrogen-nitrate and phosor- phosphate in each selected culture and municipal wastewater in each species of green algae at 25 C? and a light intensity 380 µ E / m2 / s.